Analisis Pengaruh Efektivitas Penerapan Teknologi Biometrik, Persepsi Kegunaan, dan Persepsi Kemudahan terhadap Peningkatan Penggunaan Teknologi Biometrik di Bandara dengan Kepuasan Pelanggan sebagai Variabel Intervening - Fikri, Muhammad; Setia Kurniawan, Jermanto; Tatiana, Yana; Abidin, Zaenal (Syntax Corporation, 2025)
This study aims to analyze the effectiveness of the application of biometric technology, the perception of usability, and the perception of ease of use on the increase in the use of biometric technology at airports, with customer satisfaction as an intervening variable. Although biometric technologies such as facial recognition and fingerprints have been shown to improve aviation efficiency and security in various countries, their adoption rate in Indonesia is still low. This study uses a quantitative approach with a survey method of 200 respondents using the biometric system at Soekarno-Hatta Airport. The research instrument was tested for validity and reliability, and the data were analyzed using multiple linear regression and the Sobel mediation test. The results showed that the effectiveness of implementation, usability perception, and convenience perception significantly affected the increase in the use of biometric technology, with usability perception as the dominant factor. Customer satisfaction has been shown to strengthen the relationship between these three variables and technology adoption. These findings show that convenience, speed of service, and clarity of the benefits of technology are key factors in encouraging users to return to using biometric systems. The practical implications of this study include recommendations for simplifying the interface, improving user literacy, and strengthening data protection regulations. This research contributes to the development of the transportation management literature and reception technology and provides a foundation for policymakers to increase public confidence in biometric services in the aviation sector.